Reconquering the conquest - Ignatieff, Michael (Primedia Productions, 1993)
Examines how French-speaking Canadians struggle to obtain independence for Québec while trying to prevent the Cree Indians from claiming the same territory. Host, Michael Ignatieff. Photographers, Brian McDairmant, Andy Binnington, Ralph MacDonald editors, Mark George, Tim Kruydenberg music, Gordon Durity.